2019
DOI: 10.1039/c8mh01208c
|View full text |Cite
|
Sign up to set email alerts
|

3D-printable self-healing and mechanically reinforced hydrogels with host–guest non-covalent interactions integrated into covalently linked networks

Abstract: Novel 3D-printable hydrogels with host–guest non-covalent interactions and covalently crosslinked networks show robust mechanical strength, self-healing performance and excellent biocompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 179 publications
(109 citation statements)
references
References 63 publications
1
101
0
1
Order By: Relevance
“…The shape stability of the printed features could be significantly enhanced through a second step of covalent crosslinking. For example, through photoinitiated covalent crosslinking, [ 86,91,94,95,102–105 ] strong ionic interactions of alginate with calcium, [ 92,101,106 ] or horseradish peroxidase/hydrogen peroxide crosslinking (H 2 O 2 ). [ 95 ] Burdick and co‐workers reported that despite achieving 3D layer‐by‐layer grid structures using hydrogels crosslinked with only a supramolecular network, the filaments were still fused together when printing multilayers due to the dynamic nature of supramolecular interactions (Figure 3D).…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The shape stability of the printed features could be significantly enhanced through a second step of covalent crosslinking. For example, through photoinitiated covalent crosslinking, [ 86,91,94,95,102–105 ] strong ionic interactions of alginate with calcium, [ 92,101,106 ] or horseradish peroxidase/hydrogen peroxide crosslinking (H 2 O 2 ). [ 95 ] Burdick and co‐workers reported that despite achieving 3D layer‐by‐layer grid structures using hydrogels crosslinked with only a supramolecular network, the filaments were still fused together when printing multilayers due to the dynamic nature of supramolecular interactions (Figure 3D).…”
Section: Materials Designs For 3d Printabilitymentioning
confidence: 99%
“…Besides excellent mechanical properties and self‐healing, the biocompatibility of 3D printable polymers could be achieved through constructing the double network consisting of host–guest interaction and covalent bonds. [ 105 ]…”
Section: Retaining Materials Properties Of Printed Polymersmentioning
confidence: 99%
“…Unfortunately, cartilage is an avascular and nervefree tissue, and its healing/self-regeneration upon damage remains a significant clinical challenge 3 . To date, various hydrogel systems, such as injectable hydrogels 4 and 3D printed cell-laden hydrogels 5 , have been deployed as bioscaffolds for articular cartilage tissue engineering 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the low‐cost, green, and high‐efficiency fabrication of self‐healing materials should be developed in further research. 3D printing, as a promising manufacturing technology, which can be used to fabricate multiscale constructs via smart control systems and recently, the self‐healing biocompatible hydrogels fabricated by 3D printing have been reported . Compared with traditional hydrogels, the 3D‐printed hydrogel scaffolds exhibited special and homogeneous porous structures, therefore, in this case, the combination of 3D printed nanostructure and self‐healing will enhance the interfacial properties of materials.…”
Section: Discussionmentioning
confidence: 99%